The Nexus of Perceived Test Validity and Test Fairness on Students Mental Well-Being in Learning Outcomes - Muhammad Bukhori Dalimunthe; Deni Adriani; Dhea Yurike Silaban; Rani Selfia Sipayung; Ruhama Girsang (Journal of Education and Teaching Learning, 2026)
This study aims to examine the effect of students’ perceptions of test validity and fairness on their mental well-being in the context of learning outcomes. The background of this study is based on the increasing academic pressure originating from evaluation systems and the importance of students’ psychological well-being as a foundation for effective learning. The approach used is quantitative with a multiple linear regression method. The population of this study is all tenth-grade students of SMA Negeri 1 Silimakuta, with a sample of 32 respondents selected through a non-probability sampling technique. The research instrument is a five-level Likert-scale questionnaire consisting of 18 statement items. The analysis results show that partially, perceived test validity has a significant effect on students’ mental well-being (t stat=5.246 > t table=2.04; sig.=0.000). On the contrary, perceived test fairness does not show a significant effect (t stat=-1.068 < t table=2.04; sig.=0.294). However, simultaneously both variables have a significant effect on students’ mental well-being (F stat=22.435 > F table=3.33; sig.=0.000) with a contribution of 60.7% (R square=0.607). These findings indicate that an evaluation system that is valid and perceived as fair together is able to create a learning environment that supports students’ psychological well-being. Thus, this study emphasizes the importance of designing learning outcomes that not only fulfills psychometric aspects but also pays attention to the emotional and psychological impacts of learners.